LDH-A inhibitor as a remedy to potentiate the anticancer effect of docetaxel in prostate cancer - Çakıcı, Çağrı; Daylan, Benay; Ünlüer, Rüveyde Safiye; Emekli Alturfan, Ebru; Ayla, Şule; Eren Gözel, Hilal; Yiğit, Pakize; Yavuz Dokgöz, Elif; Yiğitbaşı, Türkan (Ivyspring International Publisher, 2024)
Increased LDH-A activity promotes tumor growth, migration, invasion, and metastasis. This study aimed to investigate the effects of the combination of LDH-A inhibitor and Docetaxel on apoptosis and epithelial-mesenchymal transition (EMT) in the murine prostate cancer (PCa) model. The prostate cancer murine model was developed subcutaneously in 50 male B57CL/6 mice using the Tramp-C2 prostate cancer cell line. From the tumor tissue samples, apoptosis analysis was performed using TUNEL staining, and EMT was investigated using western blot and qPCR. Hematoxylin-eosin staining (HE) and Periodic acid-Schiff staining were used to histopathologically examine liver and kidney tissues. Lactate levels revealed that the Warburg effect was reversed with the LDH-A inhibitor. Both serum and tumor tissue apoptosis increased, and tumor sizes reduced in PCa+LDH-A inhibitor + Docetaxel treatment groups (p<0.05). The combination of LDH-A inhibitor and Docetaxel inhibited EMT mechanism by causing a decrease in Snail, Slug, Twist, and HIF-1? expressions as well as a decrease in N-cadherin and an increase in E-cadherin levels. Reprogramming glucose metabolism with an LDH-A inhibitor can increase the effectiveness of Docetaxel on apoptosis and metastasis mechanisms in PCa.
Keywords: Apoptosis; EMT; LDH-A Inhibitor; Prostate Cancer; Warburg Effect